Regulation of eosinophil recruitment and allergic airway inflammation by heparan sulfate proteoglycan (HSPG) modifying enzymes. (7th February 2018) - Ge, Xiao Na; Bastan, Idil; Ha, Sung Gil; Greenberg, Yana G.; Esko, Jeffrey D.; Rao, Savita P.; Sriramarao, P.
ABSTRACT: Background: HSPGs are glycoproteins containing covalently attached heparan sulfate (HS) chains which bind to growth factors, chemokines, etc., and regulate various aspects of inflammation including cell recruitment. We previously showed that deletion of endothelial N -acetylglucosamine N -deacetylase- N -sulfotransferase-1 (Ndst1), an enzyme responsible for N -sulfation during HS biosynthesis, reduces allergic airway inflammation (AAI). Here, we investigated the importance of O -sulfation mediated by uronyl 2- O -sulfotransferase (Hs2st) in development of AAI relative to N -sulfation.Methods: Mice deficient in endothelial and leukocyte Hs2st ( Hs2st f/f Tie2Cre + ) or Ndst1 ( Ndst1 f/f Tie2Cre + ) and WT mice were challenged with Alternaria alternata and evaluated for airway inflammation. Trafficking of murine eosinophils on lung endothelial cells was examined in vitro under conditions of flow.Results: Exposure to Alternaria decreased expression level of Hs2st in WT mice while level of Ndst1 remained unchanged. Compared to WT mice, Alternaria -challenged Hs2st f/f Tie2Cre + mice exhibited significantly increased eosinophils in the bone marrow, bronchoalveolar lavage fluid [BALF] and lung tissue associated with persistent airway hyperresponsiveness, airway mucus hypersecretion and elevated Th2 cytokines. In contrast, Alternaria -challenged Ndst1 f/f Tie2Cre + mice exhibited a marked reduction in airway eosinophilia, mucus secretion and smooth muscle mass compared to WT counterparts. While BALF eotaxins were lower in Alternaria -challenged Hs2st f/f Tie2Cre + relative to WT mice, they were not reduced to background levels as in allergen-challenged Ndst1 f/f Tie2Cre + mice. Trafficking of murine eosinophils under conditions of flow in vitro was similar on Hs2st -deficient and WT endothelial cells. Expression of ZO-1 in Hs2st -deficient lung blood vessels in control and allergen-challenged mice was significantly lower than in WT counterparts.Conclusions: Our study demonstrates that allergen exposure reduces expression of Hs2st; loss of uronyl 2- O -sulfation in endothelial and leukocyte HSPG amplifies recruitment of eosinophils likely due to a compromised vascular endothelium resulting in persistent inflammation whereas loss of N -sulfation limits eosinophilia and attenuates inflammation underscoring the importance of site-specific sulfation in HSPG to their role in AAI.